Considerations on the Application of the IAEA Safety Requirements for the Design of Nuclear Power Plants. (IAEA TECDOC Series No. 1791., 2016)
"This publication facilitates the understanding and practical application of the IAEA Safety Requirements for the Design of Nuclear Power Plants, SSR 2/1 (Rev. 1), which has been revised after the Fukushima Daiichi accident to strengthen the safety of the plant designs. It addresses in particular some novel requirements and concepts in SSR-2/1 (Rev. 1), that due to the complexity of the topics could lead to different interpretations. The publication is intended to clarify them in order to contribute to the harmonization of approaches and to coalesce or minimize diverging views."--Publisher's description